ANALISIS PEMAHAMAN MATEMATIS SISWA SMPN 3 BOJONEGORO PADA MATERI PELUANG BERDASARKAN TEORI APOS - Rista Aprillia; Ari Indriani; Dwi Erna Novianti (IKIP PGRI Bojonegoro, 2022)
The research was carried out by researchers with the aim of analyzing the mathematical understanding of the students of SMPN 3 Bojonegoro on the probability material based on the APOS theory. This research method is qualitative by using a qualitative descriptive approach with the researcher acting as the key instrument or main instrument. Based on the results of the analysis of mathematical understanding of students at SMPN 3 Bojonegoro based on APOS Theory. In the framework of the action stage, the subject has a tendency to explain and present the given opportunities. Subjects in the process stage framework have a tendency to explain, present and classify questions about probability events. Subjects in the process stage framework are subjects who have a tendency to explain, present, classify and apply concepts and procedures. In the framework of the last stage, namely the framework of the schema stage, the subject has a tendency to explain, present, classify, apply and develop the concepts that have been studied. Keywords: Understanding Analysi; Mathematical Understanding; APOS Theory; Opportunity Material.